GE_GERICHTE P/14645/2024 vom 17. Juli 2025 - GE Cour de justice (2025)
RÉCUSATION;NULLITÉ;ADMINISTRATION DES PREUVES;RÉPÉTITION(ACTIVITÉ);COLLABORATEUR;DROIT D'ÊTRE ENTENDU | CPP.60; Cst.29.al2; CPP.61